Do Green Banking Practices Change Customers’ Attitudes and Behavior : A Conceptual Model - Jain, Anshul; Yadav, Priyanka; Kochhar, Khyati (Indian Journal of Finance, 2024)
Purpose : The rising importance of environmental sustainability significantly changed customers’ consumption patterns, making studying their attitudes and behavior crucial. Thus, this research created a conceptual model to identify the drivers and analyze their influence on the customers’ intention toward green banking practices. Design/Methodology/Approach : A structured questionnaire was used in conjunction with a mixed sampling technique to collect data from 540 Indian banking customers. Data collecting took into account two banks from the public and two from the private sector. The link between the constructs was implemented using structural equation modeling in AMOS 24. Findings : The analysis showed the significant influence of environmental concern (EC), environmental knowledge (EK), subjective norms (SN), trust (TR), and government regulations (GR) on the attitude (AT), and attitude also significantly influenced customers’ behavior intention (BI) toward green banking practices. A comparative analysis between the customers of public and private banks showed that only GR played a dominant role in public banks’ users. Practical Implications : The model may be tested in several settings to help academics understand how customers intend to use green goods and services. From a managerial standpoint, this study could help managers better understand how clients want to use and sustainably consume financial services. Originality/Value : This study primarily investigated the difference in BI of public and private bank users in India while considering six significant variables.